ACTIVITIES WITH AL-IHSAN THAT CONTRADICT THE CONCEPT OF QIYAS ACCORDING TO FUQAHA’: STUDIES ON JINAYAT العمل بالاستحسان المخالف للقياس عند الفقهاء: الجنايات نموذجًا - Abdualhmeed Alqahoom (Profetika: Jurnal Studi Islam, 2023)
The study of issues whose ruling differs from the original in approval embodies the realism of the Sharia, its flexibility, and the strength of its absorption of rooting and application, due to its balance between benefits and harms in the case and outcome, whether the rulings are reasonable in meaning or unreasonable in meaning. As approval and measurement are among the most important evidence on which the provisions of the Sharia are based, the research aims to study issues upon which action is made by jurists, which are contrary to the principle measured against in the rest of the rulings, by explaining the concept of working with approval that is contrary to analogy, its pretext, its controls, the basis for its work, and its status in the considered schools. Then applying it to famous and well-known issues that were practiced during the time of the Prophet, may God's prayers and peace be upon him, or the honorable companions, which are contrary to the analogy with approval, to be an origin and evidence for other issues. إن دراسة المسائل التي يختلف حكمها عن الأصل استحسانًا، يجسد واقعية الشريعة، ومرونتها، وقوة استيعابها للتأصيل والتطبيق، لموازنتها بين المصالح والمفاسد في الحال والمآل، سواء كانت الأحكام المعقولة المعنى أو غير المعقولة المعنى؛ إذ إن الاستحسان والقياس من أهم الأدلة التي أسست عليها أحكام الشريعة، فيهدف البحث إلى دراسة مسائل عليها العمل عند الفقهاء وهي مخالفة للأصل المقيس عليه في بقية الأحكام، ببيان مفهوم العمل بالاستحسان المخالف للقياس، وحجيته، وضوابطه، ومستند العمل به، ومكانته عند المذاهب المعتبرة، ثم التطبيق له بمسائل مشهورة معروفة عُمِل بها في عهد النبي صلى الله عليه وسلم، أو الصحابة الكرام، وهي مخالفة للقياس استحسانًا، لتكون أصلًا، ودليلًا، لغيرها من المسائل.